X-ray to MR: the progress of flexible instruments for endovascular navigation. (2nd August 2021) - Abdelaziz, Mohamed E M K; Tian, Libaihe; Hamady, Mohamad; Yang, Guang-Zhong; Temelkuran, Burak
Abstract: Interventional radiology and cardiology are rapidly growing areas of minimally invasive surgery, covering multiple diagnostic and interventional procedures. Treatment via endovascular techniques has become the go-to approach, thanks to its minimally invasive nature and its effectiveness in reducing hospitalisation and total time to recovery when compared to open surgery. Although x-ray fluoroscopy is currently the gold standard imaging technique for endovascular interventions, it presents occupational safety hazards to medical personnel and potential risks to patients, especially paediatric patients, because of its inherent ionising radiation. Magnetic resonance imaging (MRI), with its unique ability to provide radiation-free imaging, and acquiring morphologic and functional information, holds great promise in the advancement of image-guided navigation through the vasculature. Moreover, MRI has the potential to combine diagnosis, therapy and early evaluation of therapy in the same intervention. However, MR-guided interventions face a major challenge due to the presence of a large magnetic field (1.5/3 Tesla), which limits the set of materials suitable for the construction of key instrumentation (sheaths, catheters and guidewires). Despite these challenges, in recent years, significant progress has been made in the development of interventional devices, which comprise biocompatible, MR safe and MR visible materials. In an attempt to encourage and accelerate the development of MR-guided endovascular instrumentation, we present a systematic and illustrated overview of the plethora of work targeting to overcome the aforementioned limitations which are underpinned by the interdependent advancements in science, technology, engineering, mathematics and medicine (STEMM).